AUTHORITY OF THE HEAD OF PUBLISHING BUSINESS ESTATES LICENSES IN FOREST ADAT - ,SH, Dianto (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The purpose of this study is to analyze the relevant authority issuing permits Regional Head plantations in indigenous forest, plantation business licensing mechanism based on the laws and regulations in the jurisdiction Indonesia konsekwensi plantation business license issued by the regional heads of indigenous forest after the Constitutional Court decision No. 35 / PUU-X / 2012. This research is normative approach method legislation, Second and third approach is the concept of case-based approach. This study has also found that there was noÂ  recruitments authority to issue licenses to the head area of forest plantations in custom, there is no regulation regarding the release of forest land to indigenous forest plantation and land use juridical consequences every plantation business license issued not by the decision of the Constitutional Court No. 35 / PUU-X / 2012 is null.Keywords: Authority, licenses, customs Forest